Pagbasa, Pagsulat Tungo sa Pananaliksik - Orsal, Cesar D. (Quezon City, 2006)
A comprehensive guide designed to enhance students' skills in reading comprehension and academic writing, focusing on research methodologies and effective communication in the context of Filipino education.
Keywords: Pagsulat